Asian adaptation and validation of an English version of the multiple sclerosis international quality of life questionnaire (MusiQoL) - Thumboo, Julian; Seah, Alvin; Tan, Chong Tin; Singhal, Bhim S.; Ong, Benjamin (Academy of Medicine, Singapore, 2011)
Introduction: The Multiple Sclerosis International Quality of Life questionnaire (MusiQoL) is a self-administered, multi-dimensional, patient-based health-related quality of life (HRQoL) instrument. With increasing prevalence of multiple sclerosis (MS) in Asian countries, a valid tool to assess HRQoL in those patients is needed. The aim of this study was to evaluate patient acceptability, content validity and psychometric properties of an Asian version of the English MusiQoL in Singapore, Malaysia and India. Materials and Methods: English speaking patients older than 18 years of age with a defi nite diagnosis of MS were included. The self-administered survey material included the adapted HRQoL questionnaire, a validated generic HRQoL questionnaire: the short-form 36 (SF-36), as well as a checklist of 14 symptoms. We assessed the internal and external validity of the adapted MusiQoL. Results: A total of 81 patients with MS were included in the study. The questionnaire was generally well accepted. In the samples from Malaysia and Singapore, all scales exhibited good internal consistency (Cronbach’s alpha >0.70). Correlation to SF-36 was generally good, demonstrating high construct validity (P <0.001) in some aspects of the MusiQoL. Conclusion: The Asian adaptation of the English version of the MusiQoL in evaluating HRQoL seems to be a valid, reliable tool with adequate patient acceptability and internal consistency.